The bounded heavens: defining the limits of astrological practice in the Iberian indices. - Ribeiro, Luís Campos (Annals of Science, 2020)
This paper explores the rules for the expurgation of texts of astrology in the Iberian Indices of forbidden books. It addresses the prohibitions put forward in Rule IX of the Index of Trent and the bull Coeli et terrae of Sixtus V, and studies its impact on the rules and their interpretation in the Spanish and Portuguese Indices, in particular, those published in the first decades of the seventeenth century: the Spanish Index librorum prohibitorum et expurgatorum of 1612 and the Portuguese Index auctorum damnatae memoriae of 1624. It shows how these indices offer a more meticulous examination of the prohibitions providing not only more detail regarding the different practices of astrology, but also explicitly accept the doctrine of inclinations of Thomas Aquinas as a central rule to deal with astrological judgments on human behaviour. It also highlights some specific details of the practice of censorship of astrological books by examining case studies of censored Portuguese and Spanish astrological publications. These provide new dimensions and highlight significant differences between the theoretical rules, practical guidelines, and actual restriction of astrological content.